Environmental And Family Approach on Stunting: A Literature Review - Nur Sefa Arief Hermawan; Mareza Yolanda Umar; Feri Agustriyani (Universitas Aisyah Pringsewu, 2023)
Stunting is still a hot issue at this time due to the many factors that cause stunting and the many impacts that can occur due to stunting. This literature study aims to find the latest evidence regarding the environment and the family's approach to stunting. A total of 10 journals were obtained in the making of this systematic literature review where in the selection process it was required to use quality journals so that the journals sought in this study were journals that were in English and had clear research results. This study found that countries that are widely used as stunting research sites are countries that have a high incidence of stunting and the environment plays an important role in the incidence of stunting with many research approaches using mixed methods. There is still a lack of research that uses a family approach in researching the causes of stunting, so it is necessary to dig deeper into the family approach to stunting.Abstrak: Stunting masih merupakan issue hangat yang terjadi pada saat ini dikarenakan banyaknya faktor penyebab terjadinya stunting dan banyaknya dampak yang dapat terjadi akibat stunting. Studi literature ini bertujuan untuk mencari bukti terkini terkait lingkungan dan pendekatan keluarga terhadap kejadian stunting. Sebanyak 10 jurnal didapatkan dalam pembuatan systematic literature review ini dimana dalam proses seleksinya diharuskan untuk menggunakan jurnal yang berkualitas sehingga Jurnal yang dicari pada studi ini adalah jurnal yang berbahasa inggris dan yang mempunyai hasil penelitian yang jelas. Studi ini mendapatkan hasil bahwa negara yang banyak dijadikan tempat penelitian stunting adalah negara yang memiliki angka kejadian stunting yang cukup tinggi dan lingkungan memegang peranan penting terhadap kejadian stunting dengan banyaknya pendekatan penelitian yang menggunakan mix method. Masih kurangnya penelitian yang menggunakan pendekatan keluarga dalam penelitian penyebab terjadinya stunting sehingga perlu digali lebih dalam tentang pendekatan keluarga terhadap kejadian stunting.